Rancang Bangun Aplikasi Penjualan Genteng Berbasis Web Pada Genteng Akur Jaya Desa Pandan Sari - Rega Prastiya; Fikri Hamidy; Ajeng Savitri Puspaningrum (CV. Keranjang Teknologi Media, 2023)
Currently, the development of information technology is progressing very rapidly. It directly or indirectly affects various aspects of life, including business. Akur jaya tile is an industry engaged in clay tile located in Pandan Sari Village, Sukoharjo District, Pringsewu District, The sales process of Akur Jaya Tile in Pandan Sari village in marketing management still uses conventional methods, namely Customers must come directly to the place of the tile seller to find out the stock and price of tiles because of the lack of information obtained by the Customers often go home empty-handed because the goods are not available and have to wait a week to come back. Therefore, a web-based tile sales application is designed that aims to provide up-to-date stock and price information to customers. By using the Extreme Programming method which is divided into 4 stages, namely planning, design, coding, and testing. The system is developed using PHP and MySQL programming languages as databases to store data on the system. The system was built using Sublime text and tested using Black boxes. The system that been developed produces a website-based tile sales system that can help customers target stock and item details better than before, and produce black box testing with functional testing to the system obtained a percentage of 99% and the system is feasible to use.